Preparation method of plastic runway glue solution and plastic runway
By combining modified polyurethane, functionalized nano zinc oxide and microcrystalline cellulose, plastic runway glue with excellent water resistance and anti-aging properties was prepared, which solved the problem of insufficient mechanical properties in the existing technology and achieved higher Anti-aging, self-healing and wear resistance.
Patent Information
- Application Number
- CN202411444277.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-01-03
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing polyurethane plastic runway glue has low mechanical properties, which is difficult to meet the needs of road casting, and lacks good water resistance and anti-aging properties.
Using a combination of modified polyurethane, functionalized nano zinc oxide, microcrystalline cellulose and deionized water, a plastic runway glue solution with excellent water resistance and anti-aging properties is prepared through specific reaction steps and formulations. The specific steps include reacting isophorone diisocyanate, polytetrahydrofuran ether glycol and diol monomer to form a modified polyurethane and mixing it with functionalized nano zinc oxide and microcrystalline cellulose.
It improves the aging resistance, self-healing and water resistance of the plastic runway glue, enhances its binding ability and structural stability with the matrix, reduces damage caused by external pressure or friction, and significantly improves wear resistance.
Smart Images

Figure BDA0005087270440000031 
Figure BDA0005087270440000041 
Figure BDA0005087270440000042
Abstract
Description
Technical Field
[0001] The invention relates to the field of plastic runways, and in particular to a method for preparing a plastic runway glue solution and a plastic runway. Background Art
[0002] With the development of China's economy, the improvement of people's living standards, the vigorous development of mass fitness and the growing enthusiasm for fitness, the requirements for sports facilities are also constantly increasing, and ordinary sports venues can no longer meet the needs. Polyurethane plastic runway is a cast polyurethane product, which can be widely used in various sports venues, such as plastic track and field, tennis courts, basketball courts, etc. Compared with ordinary cinder and gravel sports venues, sports venues paved with it have the advantages of good elasticity, good shock absorption, easy cleaning and maintenance, etc., and the color can be adjusted at will, beautiful and generous, and it can effectively protect athletes from injuries. It is a good substitute for traditional sports venues.
[0003] Polyurethane used for road casting generally needs to have high mechanical properties to prevent damage after being stepped on or rolled over, and roads are often exposed to rain and sunlight, so they also need to have certain water resistance and UV aging resistance. However, the mechanical properties of general water-based polyurethane are low and difficult to meet the needs of road casting. Therefore, the present invention prepares a plastic track glue with excellent water resistance and aging resistance. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a plastic track glue and a plastic track to solve the problems existing in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0006] A plastic runway glue is obtained by mixing modified polyurethane, functionalized nano zinc oxide, microcrystalline cellulose and deionized water.
[0007] As an optimization, the modified polyurethane is obtained by reacting isophorone diisocyanate, polytetramethylene ether diol and diol monomer.
[0008] As an optimization, the polytetramethylene ether glycol model is PTMG2000, which comes from Shandong Weishang Chemical Co., Ltd.
[0009] As an optimization, the diol monomer is obtained by reacting 3,5-diformylphenylboronic acid and 4-amino-2-hydroxy-1,1,1-trifluorobutane.
[0010] As an optimization, the functionalized nano zinc oxide is obtained by reacting nano zinc oxide with hydroxymethyltriethoxysilane, polymerizing the diacid monomer and the anti-aging monomer, and then deprotecting the monomer.
[0011] As an optimization, the nano zinc oxide model is ZA-100, which comes from Hebei Bangti Chemical Co., Ltd.
[0012] As an optimization, the diacid monomer is obtained by reacting 2,3-dihydroxyterephthalic acid and 2,2-dimethoxypropane.
[0013] As an optimization, the anti-aging monomer is obtained by reacting (4-aminopyridine-2,6-diyl)dimethanol and 3,5-di-tert-butyl-4-hydroxybenzaldehyde.
[0014] A method for preparing a plastic track glue liquid comprises the following preparation steps:
[0015] (1) 2,3-dihydroxyterephthalic acid, 2,2-dimethoxypropane, p-toluenesulfonic acid and ethylenediamine are mixed in a mass ratio of 1:(0.6-0.8):(0.004-0.006):(4-6), stirred at 20-30° C. and 200-300 rpm for 4-6 hours, sodium bicarbonate in an amount of 0.2-0.3 times the mass of 2,3-dihydroxyterephthalic acid is added, stirring is continued for 15-25 minutes, then filtered, concentrated under reduced pressure, dichloromethane in an amount of 3-5 times the mass of 2,3-dihydroxyterephthalic acid is added, the mixture is allowed to stand for 1-2 hours, filtered, washed with deionized water for 3-5 times, dried with anhydrous magnesium sulfate for 15-25 minutes, concentrated under reduced pressure, and dried at 55-65° C. for 6-8 hours to obtain a diacid monomer;
[0016] (2) mixing (4-aminopyridine-2,6-diyl) dimethanol, 3,5-di-tert-butyl-4-hydroxybenzaldehyde, acetic acid and methanol in a mass ratio of 1:(1-2):(0.3-0.5):(10-20), stirring at 70-80° C. and 100-200 rpm for 23-25 h, naturally cooling to room temperature and filtering, washing with methanol and deionized water for 3-5 times respectively, and drying at 55-65° C. for 11-13 h to obtain an anti-aging monomer;
[0017] (3) Mixing nano zinc oxide and 60-70% ethanol solution in a mass ratio of 1:(15-25), ultrasonically dispersing at 20-30° C. for 25-35 min, adding 2-3 times the mass of nano zinc oxide hydroxymethyl triethoxysilane hydrolyzate at a uniform rate within 1-2 h, stirring at 150-250 r / min for 3-5 h, filtering, washing with anhydrous ethanol for 3-5 times, and drying at 35-45° C. for 4-6 h to obtain pre-modified nano zinc oxide; mixing pre-modified nano zinc oxide, diacid monomer, p-toluenesulfonic acid and tetrahydrofuran in a mass ratio of 1:(1-2):(0.1-0.2):(10-20), and stirring at 2 0-30° C., 200-300 rpm stirring for 20-30 min, adding an anti-aging monomer with a molar amount of 1 times of the diacid monomer, heating to 135-145° C. and continuing stirring for 4-6 h, naturally cooling to room temperature and filtering, washing with anhydrous ethanol and deionized water for 3-5 times respectively, drying at 65-75° C. for 6-8 h, and obtaining modified nano zinc oxide; mixing the modified nano zinc oxide, trifluoroacetic acid and methanol in a mass ratio of 1:(3-4):(15-25), stirring at 20-30° C., 100-200 rpm in a nitrogen atmosphere for 11-13 h, filtering, and heating and filtering with an oil pump for 5-7 h to obtain functionalized nano zinc oxide;
[0018] (4) 3,5-diformylphenylboric acid, glacial acetic acid and anhydrous ethanol are mixed in a mass ratio of 1:(0.01-0.02):(8-10), stirred at 100-200 rpm for 20-30 min in a nitrogen atmosphere at 45-55° C., and 4-amino-2-hydroxy-1,1,1-trifluorobutane (2 times the molar amount of 3,5-diformylphenylboric acid) is added at a uniform rate within 55-65 min, the temperature is raised to 55-65° C., and refluxed for 1-3 h, ice deionized water is added to cool until the precipitate mass remains unchanged, and then filtered, washed with anhydrous ethanol for 3-5 times, and dried at 45-55° C. for 11-13 h to obtain a diol monomer;
[0019] (5) Mix polytetrahydrofuran ether diol, diol monomer and dibutyltin dilaurate in a molar ratio of 1:(0.4-0.6):(0.01-0.02), stir for 10-20 min at 50-60° C. and 200-300 rpm in a nitrogen atmosphere, raise the temperature to 75-85° C., add isophorone diisocyanate in an amount of 1.5-2.5 times the molar amount of polytetrahydrofuran diol, continue stirring for 2-3 h, and cool to 30-40° C. to obtain a modified polyurethane;
[0020] (6) The modified polyurethane, functionalized nano zinc oxide, microcrystalline cellulose and deionized water are mixed in a mass ratio of 1:(0.03-0.05):(0.02-0.04):(0.1-0.2), and stirred at 20-30° C. and 550-650 rpm for 20-30 min to obtain a plastic track glue solution.
[0021] As an optimization, the reaction equation of the diacid monomer in step (1) is:
[0022]
[0023] As an optimization, the reaction equation of the anti-aging monomer in step (2) is:
[0024]
[0025] As an optimization, the hydroxymethyltriethoxysilane hydrolyzate in step (3) is obtained by mixing hydroxymethyltriethoxysilane and deionized water in a mass ratio of 1:124 and hydrolyzing at 25°C for 30 minutes.
[0026] As an optimization, the reaction equation of the pre-modified nano zinc oxide in step (3) is:
[0027]
[0028] As an optimization, the reaction equation of the functionalized nano zinc oxide in step (3) is:
[0029]
[0030] As an optimization, the reaction equation of the diol monomer in step (4) is:
[0031]
[0032] As an optimization, the reaction equation of the modified polyurethane in step (5) is:
[0033]
[0034] Where R1 is
[0035] As an optimization, the plastic track glue of the plastic track is the plastic track glue described in any one of claims 1 to 9.
[0036] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0037] When preparing the plastic track glue, the present invention comprises the following steps: reacting 2,3-dihydroxyterephthalic acid and 2,2-dimethoxypropane to obtain a diacid monomer; reacting (4-aminopyridine-2,6-diyl) dimethanol and 3,5-di-tert-butyl-4-hydroxybenzaldehyde to obtain an anti-aging monomer; reacting nano zinc oxide and hydroxymethyltriethoxysilane to obtain pre-modified nano zinc oxide; polymerizing the pre-modified nano zinc oxide, the diacid monomer and the anti-aging monomer, and then deprotecting to obtain functionalized nano zinc oxide; reacting 3,5-diformylphenylboric acid and 4-amino-2-hydroxy-1,1,1-trifluorobutane to obtain a diol monomer; reacting isophorone diisocyanate, polytetramethylene glycol and the diol monomer to obtain a modified polyurethane; and mixing the modified polyurethane, the functionalized nano zinc oxide, microcrystalline cellulose and deionized water to obtain the plastic track glue.
[0038] First, 2,3-dihydroxyterephthalic acid and 2,2-dimethoxypropane are reacted to obtain a diacid monomer; (4-aminopyridine-2,6-diyl) dimethanol and 3,5-di-tert-butyl-4-hydroxybenzaldehyde are reacted to obtain an anti-aging monomer; nano zinc oxide and hydroxymethyltriethoxysilane are reacted to obtain pre-modified nano zinc oxide; the pre-modified nano zinc oxide, the diacid monomer and the anti-aging monomer are polymerized and then deprotected to obtain functionalized nano zinc oxide; 2,2-dimethoxypropane is used to protect the catechol bond on 2,3-dihydroxyterephthalic acid; The structure is formed to avoid the influence of subsequent esterification reaction. After the reaction is completed, the protection is removed to form a reversible borate ester bond with the boric acid group on the modified polyurethane, and a covalent cross-linked network of borate ester bonds is constructed to improve self-healing properties. Diacid monomers and anti-aging monomers are polymerized on the surface of pre-modified nano-zinc oxide, and a hindered phenol structure that can capture free radicals is introduced on the nano-zinc oxide, which cooperates with the effect of nano-zinc oxide in shielding and scattering ultraviolet light to improve anti-aging properties. At the same time, the pyridine in the anti-aging monomer can complex metal ions, enhance the bonding ability of the runway rubber with the matrix, and improve wear resistance.
[0039] Secondly, 3,5-diformylphenylboronic acid and 4-amino-2-hydroxy-1,1,1-trifluorobutane are reacted to obtain a diol monomer; then isophorone diisocyanate, polytetramethylene glycol and diol monomer are reacted to obtain modified polyurethane; the modified polyurethane, functionalized nano zinc oxide, microcrystalline cellulose and deionized water are mixed to obtain a plastic track glue; the diol monomer obtained by Schiff base reaction participates in the polymerization of the polyurethane main chain, and boric acid groups and trifluoromethyl groups are introduced to react with catechol and 1,3-diol to form a boric acid ester bond covalent cross-linked network to improve the self-healing performance; at the same time, the highly electronegative and highly stable carbon-fluorine bond can improve water resistance; the 1,3-diol structure on the microcrystalline cellulose is used to form a reversible boric acid ester bond with the boric acid group to increase the boric acid ester bond covalent cross-linked network, and at the same time, the cellulose self-cross-linked network can improve the structural stability, reduce the damage caused by external pressure or friction, and further improve the self-healing and wear resistance. DETAILED DESCRIPTION
[0040] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0041] Example 1
[0042] A method for preparing a plastic runway glue liquid, the method comprising the following preparation steps:
[0043] (1) 2,3-dihydroxyterephthalic acid, 2,2-dimethoxypropane, p-toluenesulfonic acid and ethylenediamine were mixed in a mass ratio of 1:0.6:0.004:4, stirred at 20° C. and 200 rpm for 6 h, added with sodium bicarbonate in an amount of 0.2 times the mass of 2,3-dihydroxyterephthalic acid, continued to stir for 25 min, filtered, concentrated under reduced pressure, added with dichloromethane in an amount of 3 times the mass of 2,3-dihydroxyterephthalic acid, allowed to stand for 2 h, filtered, washed with deionized water 3 times, dried with anhydrous magnesium sulfate for 15 min, concentrated under reduced pressure, and dried at 55° C. for 8 h to obtain a diacid monomer;
[0044] (2) (4-aminopyridine-2,6-diyl) dimethanol, 3,5-di-tert-butyl-4-hydroxybenzaldehyde, acetic acid and methanol were mixed in a mass ratio of 1:1:0.3:10, stirred at 70°C and 100 rpm for 25 hours, naturally cooled to room temperature and filtered, washed with methanol and deionized water for three times respectively, and dried at 55°C for 13 hours to obtain an anti-aging monomer;
[0045] (3) Mixing nano zinc oxide and 60% ethanol solution in a mass ratio of 1:15, ultrasonically dispersing at 20°C for 35 minutes, adding 3 times the mass of nano zinc oxide hydroxymethyl triethoxysilane hydrolyzate at a uniform rate within 1 hour, stirring at 150 r / min for 5 hours, filtering, washing with anhydrous ethanol for 3 times, and drying at 35°C for 6 hours to obtain pre-modified nano zinc oxide; mixing pre-modified nano zinc oxide, diacid monomer, p-toluenesulfonic acid and tetrahydrofuran in a mass ratio of 1:1:0.1:10, and stirring at 20°C for 35 minutes. ℃, 200rpm stirring for 30min, add anti-aging monomer with 1 times the molar amount of diacid monomer, heat to 135℃ and continue stirring for 6h, cool naturally to room temperature and filter, wash with anhydrous ethanol and deionized water for 3 times respectively, dry at 65℃ for 8h to obtain modified nano zinc oxide; mix modified nano zinc oxide, trifluoroacetic acid and methanol in a mass ratio of 1:3:15, stir for 13h at 20℃ and 100rpm in a nitrogen atmosphere and filter, heat and filter with an oil pump for 5h to obtain functionalized nano zinc oxide;
[0046] (4) 3,5-diformylphenylboric acid, glacial acetic acid and anhydrous ethanol were mixed in a mass ratio of 1:0.01:8, stirred at 45°C and 100 rpm for 30 min in a nitrogen atmosphere, and 4-amino-2-hydroxy-1,1,1-trifluorobutane (2 times the molar amount of 3,5-diformylphenylboric acid) was added at a uniform rate within 55 min, the temperature was raised to 55°C and refluxed for 3 h, ice deionized water was added and cooled until the precipitate mass remained unchanged, then filtered, washed with anhydrous ethanol 3 times, and dried at 45°C for 13 h to obtain a diol monomer;
[0047] (5) polytetrahydrofuran ether diol, diol monomer and dibutyltin dilaurate were mixed in a molar ratio of 1:0.4:0.01, stirred at 50°C and 200 rpm for 20 min in a nitrogen atmosphere, heated to 75°C, added with 1.5 times the molar amount of isophorone diisocyanate of polytetrahydrofuran diol, continued stirring for 3 h, and cooled to 30°C to obtain a modified polyurethane;
[0048] (6) The modified polyurethane, functionalized nano zinc oxide, microcrystalline cellulose and deionized water were mixed in a mass ratio of 1:0.03:0.02:0.1, and stirred at 20°C and 550 rpm for 30 min to obtain a plastic track glue.
[0049] Example 2
[0050] A method for preparing a plastic runway glue liquid, the method comprising the following preparation steps:
[0051] (1) 2,3-dihydroxyterephthalic acid, 2,2-dimethoxypropane, p-toluenesulfonic acid and ethylenediamine were mixed in a mass ratio of 1:0.7:0.005:5, stirred at 25°C and 250 rpm for 5 hours, added with sodium bicarbonate in an amount of 0.25 times the mass of 2,3-dihydroxyterephthalic acid, continued to stir for 20 minutes, filtered, concentrated under reduced pressure, added with dichloromethane in an amount of 4 times the mass of 2,3-dihydroxyterephthalic acid, allowed to stand for 1.5 hours, filtered, washed with deionized water 4 times, dried with anhydrous magnesium sulfate for 20 minutes, concentrated under reduced pressure, and dried at 60°C for 7 hours to obtain a diacid monomer;
[0052] (2) (4-aminopyridine-2,6-diyl) dimethanol, 3,5-di-tert-butyl-4-hydroxybenzaldehyde, acetic acid and methanol were mixed in a mass ratio of 1:1.5:0.4:15, stirred at 75°C and 150 rpm for 24 hours, naturally cooled to room temperature and filtered, washed with methanol and deionized water for 4 times respectively, and dried at 60°C for 12 hours to obtain an anti-aging monomer;
[0053] (3) Mixing nano zinc oxide and 65% ethanol solution at a mass ratio of 1:20, ultrasonically dispersing at 25° C. for 30 min, adding 2.5 times the mass of nano zinc oxide hydroxymethyl triethoxysilane hydrolyzate at a uniform rate within 1.5 h, stirring at 200 r / min for 4 h, filtering, washing with anhydrous ethanol for 4 times, and drying at 40° C. for 5 h to obtain pre-modified nano zinc oxide; mixing pre-modified nano zinc oxide, diacid monomer, p-toluenesulfonic acid and tetrahydrofuran at a mass ratio of 1:1.5:0.15:15, Stir at 25°C and 250rpm for 25min, add an anti-aging monomer with a molar amount of 1 times that of the diacid monomer, heat to 140°C and continue stirring for 5h, cool naturally to room temperature and filter, wash with anhydrous ethanol and deionized water for 4 times respectively, and dry at 70°C for 7h to obtain modified nano zinc oxide; mix the modified nano zinc oxide, trifluoroacetic acid and methanol in a mass ratio of 1:3.5:20, stir at 25°C and 150rpm in a nitrogen atmosphere for 12h, filter, and heat and filter with an oil pump for 6h to obtain functionalized nano zinc oxide;
[0054] (4) 3,5-diformylphenylboric acid, glacial acetic acid and anhydrous ethanol were mixed in a mass ratio of 1:0.015:9, stirred at 50°C and 150 rpm for 25 min in a nitrogen atmosphere, and 4-amino-2-hydroxy-1,1,1-trifluorobutane (2 times the molar amount of 3,5-diformylphenylboric acid) was added at a uniform rate within 60 min, the temperature was raised to 60°C and refluxed for 2 h, ice deionized water was added and cooled until the precipitate mass remained unchanged, then filtered, washed with anhydrous ethanol 4 times, and dried at 50°C for 12 h to obtain a diol monomer;
[0055] (5) polytetrahydrofuran ether diol, diol monomer and dibutyltin dilaurate were mixed in a molar ratio of 1:0.5:0.015, stirred at 55°C and 250 rpm for 15 min in a nitrogen atmosphere, heated to 80°C, and added with isophorone diisocyanate in an amount twice the molar amount of polytetrahydrofuran diol, and stirred for 2.5 h, and cooled to 35°C to obtain a modified polyurethane;
[0056] (6) The modified polyurethane, functionalized nano zinc oxide, microcrystalline cellulose and deionized water were mixed in a mass ratio of 1:0.04:0.03:0.15, and stirred at 25°C and 600 rpm for 25 min to obtain a plastic track glue solution.
[0057] Example 3
[0058] A method for preparing a plastic runway glue liquid, the method comprising the following preparation steps:
[0059] (1) 2,3-dihydroxyterephthalic acid, 2,2-dimethoxypropane, p-toluenesulfonic acid and ethylenediamine were mixed in a mass ratio of 1:0.8:0.006:6, stirred at 30° C. and 300 rpm for 4 h, added with sodium bicarbonate in an amount of 0.3 times the mass of 2,3-dihydroxyterephthalic acid, continued to stir for 15 min, filtered, concentrated under reduced pressure, added with dichloromethane in an amount of 5 times the mass of 2,3-dihydroxyterephthalic acid, allowed to stand for 1 h, filtered, washed with deionized water 5 times, dried with anhydrous magnesium sulfate for 25 min, concentrated under reduced pressure, and dried at 65° C. for 6 h to obtain a diacid monomer;
[0060] (2) (4-aminopyridine-2,6-diyl) dimethanol, 3,5-di-tert-butyl-4-hydroxybenzaldehyde, acetic acid and methanol were mixed in a mass ratio of 1:2:0.5:20, stirred at 80°C and 200 rpm for 23 hours, naturally cooled to room temperature and filtered, washed with methanol and deionized water for 5 times respectively, and dried at 65°C for 11 hours to obtain an anti-aging monomer;
[0061] (3) Nano zinc oxide and 70% ethanol solution by volume were mixed in a mass ratio of 1:25, ultrasonically dispersed at 30°C for 25 minutes, and hydroxymethyl triethoxysilane hydrolyzate with a mass twice that of nano zinc oxide was added at a uniform rate within 2 hours. After stirring at 250 r / min for 3 hours, the mixture was filtered, washed with anhydrous ethanol for 5 times, and dried at 45°C for 4 hours to obtain pre-modified nano zinc oxide; the pre-modified nano zinc oxide, diacid monomer, p-toluenesulfonic acid and tetrahydrofuran were mixed in a mass ratio of 1:2:0.2:20, and heated at 30°C for 2 hours. ℃, 300rpm stirring for 20min, add anti-aging monomer with 1 times the molar amount of diacid monomer, heat to 145℃ and continue stirring for 4h, cool naturally to room temperature and filter, wash with anhydrous ethanol and deionized water for 5 times respectively, dry at 75℃ for 6h to obtain modified nano zinc oxide; mix modified nano zinc oxide, trifluoroacetic acid and methanol in a mass ratio of 1:4:25, stir for 11h at 30℃ and 200rpm in a nitrogen atmosphere and filter, heat and filter with an oil pump for 7h to obtain functionalized nano zinc oxide;
[0062] (4) 3,5-diformylphenylboric acid, glacial acetic acid and anhydrous ethanol were mixed in a mass ratio of 1:0.02:10, stirred at 55°C and 200 rpm for 20 min in a nitrogen atmosphere, and 4-amino-2-hydroxy-1,1,1-trifluorobutane (2 times the molar amount of 3,5-diformylphenylboric acid) was added at a uniform rate within 65 min, the temperature was raised to 65°C and refluxed for 1 h, ice deionized water was added and cooled until the mass of the precipitate remained unchanged, then filtered, washed with anhydrous ethanol 5 times, and dried at 55°C for 11 h to obtain a diol monomer;
[0063] (5) polytetrahydrofuran ether diol, diol monomer and dibutyltin dilaurate were mixed in a molar ratio of 1:0.6:0.02, stirred at 60°C and 300 rpm for 10 min in a nitrogen atmosphere, heated to 85°C, and 2.5 times the molar amount of isophorone diisocyanate as polytetrahydrofuran diol was added, and stirred for 2 h, and the temperature was lowered to 40°C to obtain a modified polyurethane;
[0064] (6) The modified polyurethane, functionalized nano zinc oxide, microcrystalline cellulose and deionized water were mixed in a mass ratio of 1:0.05:0.04:0.2, and stirred at 30°C and 650 rpm for 20 min to obtain a plastic track glue.
[0065] Comparative Example 1
[0066] A method for preparing a plastic runway glue liquid, the method comprising the following preparation steps:
[0067] (1) 2,3-dihydroxyterephthalic acid, 2,2-dimethoxypropane, p-toluenesulfonic acid and ethylenediamine were mixed in a mass ratio of 1:0.7:0.005:5, stirred at 25°C and 250 rpm for 5 hours, added with sodium bicarbonate in an amount of 0.25 times the mass of 2,3-dihydroxyterephthalic acid, continued to stir for 20 minutes, filtered, concentrated under reduced pressure, added with dichloromethane in an amount of 4 times the mass of 2,3-dihydroxyterephthalic acid, allowed to stand for 1.5 hours, filtered, washed with deionized water 4 times, dried with anhydrous magnesium sulfate for 20 minutes, concentrated under reduced pressure, and dried at 60°C for 7 hours to obtain a diacid monomer;
[0068] (2) Nano zinc oxide and 65% ethanol solution by volume were mixed in a mass ratio of 1:20, ultrasonically dispersed at 25°C for 30 minutes, and 2.5 times the mass of nano zinc oxide hydroxymethyl triethoxysilane hydrolyzate was added at a uniform rate within 1.5 hours. After stirring at 200 r / min for 4 hours, the mixture was filtered, washed with anhydrous ethanol for 4 times, and dried at 40°C for 5 hours to obtain pre-modified nano zinc oxide; the pre-modified nano zinc oxide, diacid monomer, p-toluenesulfonic acid and tetrahydrofuran were mixed in a mass ratio of 1:1.5:0.15:15, and heated at 25°C, 25 0rpm and stirred for 25min, (4-aminopyridine-2,6-diyl) dimethanol with a molar amount of 1 times of the diacid monomer was added, the temperature was raised to 140℃ and stirred for 5h, naturally cooled to room temperature and filtered, washed with anhydrous ethanol and deionized water for 4 times respectively, and dried at 70℃ for 7h to obtain modified nano zinc oxide; modified nano zinc oxide, trifluoroacetic acid and methanol were mixed in a mass ratio of 1:3.5:20, stirred for 12h at 25℃ and 150rpm in a nitrogen atmosphere, filtered, and heated and filtered with an oil pump for 6h to obtain functionalized nano zinc oxide;
[0069] (3) 3,5-diformylphenylboric acid, glacial acetic acid and anhydrous ethanol were mixed in a mass ratio of 1:0.015:9, stirred at 50°C and 150 rpm for 25 min in a nitrogen atmosphere, and 4-amino-2-hydroxy-1,1,1-trifluorobutane (2 times the molar amount of 3,5-diformylphenylboric acid) was added at a uniform rate within 60 min, the temperature was raised to 60°C and refluxed for 2 h, ice deionized water was added and cooled until the precipitate mass remained unchanged, then filtered, washed with anhydrous ethanol 4 times, and dried at 50°C for 12 h to obtain a diol monomer;
[0070] (4) polytetrahydrofuran ether diol, diol monomer and dibutyltin dilaurate were mixed in a molar ratio of 1:0.5:0.015, stirred at 55°C and 250 rpm for 15 min in a nitrogen atmosphere, heated to 80°C, and added with isophorone diisocyanate in an amount twice the molar amount of polytetrahydrofuran diol, and stirred for 2.5 h, and cooled to 35°C to obtain a modified polyurethane;
[0071] (5) The modified polyurethane, functionalized nano zinc oxide, microcrystalline cellulose and deionized water were mixed in a mass ratio of 1:0.04:0.03:0.15, and stirred at 25°C and 600 rpm for 25 min to obtain a plastic track glue solution.
[0072] Comparative Example 2
[0073] A method for preparing a plastic runway glue liquid, the method comprising the following preparation steps:
[0074] (1) 2,3-dihydroxyterephthalic acid, 2,2-dimethoxypropane, p-toluenesulfonic acid and ethylenediamine were mixed in a mass ratio of 1:0.7:0.005:5, stirred at 25°C and 250 rpm for 5 hours, added with sodium bicarbonate in an amount of 0.25 times the mass of 2,3-dihydroxyterephthalic acid, continued to stir for 20 minutes, filtered, concentrated under reduced pressure, added with dichloromethane in an amount of 4 times the mass of 2,3-dihydroxyterephthalic acid, allowed to stand for 1.5 hours, filtered, washed with deionized water 4 times, dried with anhydrous magnesium sulfate for 20 minutes, concentrated under reduced pressure, and dried at 60°C for 7 hours to obtain a diacid monomer;
[0075] (2) Mixing nano zinc oxide and 65% ethanol solution in a mass ratio of 1:20, ultrasonically dispersing at 25° C. for 30 min, adding 2.5 times the mass of nano zinc oxide hydroxymethyl triethoxysilane hydrolyzate at a uniform rate within 1.5 h, stirring at 200 r / min for 4 h, filtering, washing with anhydrous ethanol for 4 times, and drying at 40° C. for 5 h to obtain pre-modified nano zinc oxide; mixing pre-modified nano zinc oxide, diacid monomer, p-toluenesulfonic acid and tetrahydrofuran in a mass ratio of 1:1.5:0 .15:15, stir at 25°C and 250rpm for 25min, heat to 140°C and continue stirring for 5h, cool naturally to room temperature and filter, wash with anhydrous ethanol and deionized water for 4 times respectively, dry at 70°C for 7h to obtain modified nano zinc oxide; mix modified nano zinc oxide, trifluoroacetic acid and methanol in a mass ratio of 1:3.5:20, stir at 25°C and 150rpm for 12h in a nitrogen atmosphere and filter, heat and filter with an oil pump for 6h to obtain functionalized nano zinc oxide;
[0076] (3) 3,5-diformylphenylboric acid, glacial acetic acid and anhydrous ethanol were mixed in a mass ratio of 1:0.015:9, stirred at 50°C and 150 rpm for 25 min in a nitrogen atmosphere, and 4-amino-2-hydroxy-1,1,1-trifluorobutane (2 times the molar amount of 3,5-diformylphenylboric acid) was added at a uniform rate within 60 min, the temperature was raised to 60°C and refluxed for 2 h, ice deionized water was added and cooled until the precipitate mass remained unchanged, then filtered, washed with anhydrous ethanol 4 times, and dried at 50°C for 12 h to obtain a diol monomer;
[0077] (4) polytetrahydrofuran ether diol, diol monomer and dibutyltin dilaurate were mixed in a molar ratio of 1:0.5:0.015, stirred at 55°C and 250 rpm for 15 min in a nitrogen atmosphere, heated to 80°C, and added with isophorone diisocyanate in an amount twice the molar amount of polytetrahydrofuran diol, and stirred for 2.5 h, and cooled to 35°C to obtain a modified polyurethane;
[0078] (5) The modified polyurethane, functionalized nano zinc oxide, microcrystalline cellulose and deionized water were mixed in a mass ratio of 1:0.04:0.03:0.15, and stirred at 25°C and 600 rpm for 25 min to obtain a plastic track glue solution.
[0079] Comparative Example 3
[0080] A method for preparing a plastic runway glue liquid, the method comprising the following preparation steps:
[0081] (1) (4-aminopyridine-2,6-diyl) dimethanol, 3,5-di-tert-butyl-4-hydroxybenzaldehyde, acetic acid and methanol were mixed in a mass ratio of 1:1.5:0.4:15, stirred at 75°C and 150 rpm for 24 hours, naturally cooled to room temperature and filtered, washed with methanol and deionized water for 4 times respectively, and dried at 60°C for 12 hours to obtain an anti-aging monomer;
[0082] (2) Mixing nano zinc oxide and 65% ethanol solution in a mass ratio of 1:20, ultrasonically dispersing at 25° C. for 30 min, adding 2.5 times the mass of nano zinc oxide hydroxymethyl triethoxysilane hydrolyzate at a uniform rate within 1.5 h, stirring at 200 r / min for 4 h, filtering, washing with anhydrous ethanol for 4 times, and drying at 40° C. for 5 h to obtain pre-modified nano zinc oxide; mixing pre-modified nano zinc oxide, 2,3-dihydroxyterephthalic acid, p-toluenesulfonic acid and tetrahydrofuran in a mass ratio of 1:1.5:0.15:1 5. Mix well, stir at 25°C and 250rpm for 25min, add an anti-aging monomer with a molar amount of 1 times that of the diacid monomer, heat to 140°C and continue stirring for 5h, cool naturally to room temperature and filter, wash with anhydrous ethanol and deionized water 4 times respectively, and dry at 70°C for 7h to obtain modified nano zinc oxide; mix the modified nano zinc oxide, trifluoroacetic acid and methanol in a mass ratio of 1:3.5:20, stir at 25°C and 150rpm in a nitrogen atmosphere for 12h, filter, and heat and filter with an oil pump for 6h to obtain functionalized nano zinc oxide;
[0083] (3) 3,5-diformylphenylboric acid, glacial acetic acid and anhydrous ethanol were mixed in a mass ratio of 1:0.015:9, stirred at 50°C and 150 rpm for 25 min in a nitrogen atmosphere, and 4-amino-2-hydroxy-1,1,1-trifluorobutane (2 times the molar amount of 3,5-diformylphenylboric acid) was added at a uniform rate within 60 min, the temperature was raised to 60°C and refluxed for 2 h, ice deionized water was added and cooled until the precipitate mass remained unchanged, then filtered, washed with anhydrous ethanol 4 times, and dried at 50°C for 12 h to obtain a diol monomer;
[0084] (4) polytetrahydrofuran ether diol, diol monomer and dibutyltin dilaurate were mixed in a molar ratio of 1:0.5:0.015, stirred at 55°C and 250 rpm for 15 min in a nitrogen atmosphere, heated to 80°C, and added with isophorone diisocyanate in an amount twice the molar amount of polytetrahydrofuran diol, and stirred for 2.5 h, and cooled to 35°C to obtain a modified polyurethane;
[0085] (5) The modified polyurethane, functionalized nano zinc oxide, microcrystalline cellulose and deionized water were mixed in a mass ratio of 1:0.04:0.03:0.15, and stirred at 25°C and 600 rpm for 25 min to obtain a plastic track glue solution.
[0086] Comparative Example 4
[0087] A method for preparing a plastic runway glue liquid, the method comprising the following preparation steps:
[0088] (1) 2,3-dihydroxyterephthalic acid, 2,2-dimethoxypropane, p-toluenesulfonic acid and ethylenediamine were mixed in a mass ratio of 1:0.7:0.005:5, stirred at 25°C and 250 rpm for 5 hours, added with sodium bicarbonate in an amount of 0.25 times the mass of 2,3-dihydroxyterephthalic acid, continued to stir for 20 minutes, filtered, concentrated under reduced pressure, added with dichloromethane in an amount of 4 times the mass of 2,3-dihydroxyterephthalic acid, allowed to stand for 1.5 hours, filtered, washed with deionized water 4 times, dried with anhydrous magnesium sulfate for 20 minutes, concentrated under reduced pressure, and dried at 60°C for 7 hours to obtain a diacid monomer;
[0089] (2) (4-aminopyridine-2,6-diyl) dimethanol, 3,5-di-tert-butyl-4-hydroxybenzaldehyde, acetic acid and methanol were mixed in a mass ratio of 1:1.5:0.4:15, stirred at 75°C and 150 rpm for 24 hours, naturally cooled to room temperature and filtered, washed with methanol and deionized water for 4 times respectively, and dried at 60°C for 12 hours to obtain an anti-aging monomer;
[0090] (3) Mixing nano zinc oxide and 65% ethanol solution at a mass ratio of 1:20, ultrasonically dispersing at 25° C. for 30 min, adding 2.5 times the mass of nano zinc oxide hydroxymethyl triethoxysilane hydrolyzate at a uniform rate within 1.5 h, stirring at 200 r / min for 4 h, filtering, washing with anhydrous ethanol for 4 times, and drying at 40° C. for 5 h to obtain pre-modified nano zinc oxide; mixing pre-modified nano zinc oxide, diacid monomer, p-toluenesulfonic acid and tetrahydrofuran at a mass ratio of 1:1.5:0.15:15, Stir at 25°C and 250rpm for 25min, add an anti-aging monomer with a molar amount of 1 times that of the diacid monomer, heat to 140°C and continue stirring for 5h, cool naturally to room temperature and filter, wash with anhydrous ethanol and deionized water for 4 times respectively, and dry at 70°C for 7h to obtain modified nano zinc oxide; mix the modified nano zinc oxide, trifluoroacetic acid and methanol in a mass ratio of 1:3.5:20, stir at 25°C and 150rpm in a nitrogen atmosphere for 12h, filter, and heat and filter with an oil pump for 6h to obtain functionalized nano zinc oxide;
[0091] (4) polytetrahydrofuran ether diol and dibutyltin dilaurate were mixed in a molar ratio of 1:0.015, stirred at 55° C. and 250 rpm for 15 min in a nitrogen atmosphere, heated to 80° C., and isophorone diisocyanate in an amount twice the molar amount of polytetrahydrofuran diol was added, stirred for 2.5 h, and cooled to 35° C. to obtain a polyurethane;
[0092] (5) Polyurethane, functionalized nano zinc oxide, microcrystalline cellulose and deionized water were mixed in a mass ratio of 1:0.04:0.03:0.15, and stirred at 25° C. and 600 rpm for 25 min to obtain a plastic track glue solution.
[0093] Comparative Example 5
[0094] A method for preparing a plastic runway glue liquid, the method comprising the following preparation steps:
[0095] (1) 2,3-dihydroxyterephthalic acid, 2,2-dimethoxypropane, p-toluenesulfonic acid and ethylenediamine were mixed in a mass ratio of 1:0.7:0.005:5, stirred at 25°C and 250 rpm for 5 hours, added with sodium bicarbonate in an amount of 0.25 times the mass of 2,3-dihydroxyterephthalic acid, continued to stir for 20 minutes, filtered, concentrated under reduced pressure, added with dichloromethane in an amount of 4 times the mass of 2,3-dihydroxyterephthalic acid, allowed to stand for 1.5 hours, filtered, washed with deionized water 4 times, dried with anhydrous magnesium sulfate for 20 minutes, concentrated under reduced pressure, and dried at 60°C for 7 hours to obtain a diacid monomer;
[0096] (2) (4-aminopyridine-2,6-diyl) dimethanol, 3,5-di-tert-butyl-4-hydroxybenzaldehyde, acetic acid and methanol were mixed in a mass ratio of 1:1.5:0.4:15, stirred at 75°C and 150 rpm for 24 hours, naturally cooled to room temperature and filtered, washed with methanol and deionized water for 4 times respectively, and dried at 60°C for 12 hours to obtain an anti-aging monomer;
[0097] (3) Mixing nano zinc oxide and 65% ethanol solution at a mass ratio of 1:20, ultrasonically dispersing at 25° C. for 30 min, adding 2.5 times the mass of nano zinc oxide hydroxymethyl triethoxysilane hydrolyzate at a uniform rate within 1.5 h, stirring at 200 r / min for 4 h, filtering, washing with anhydrous ethanol for 4 times, and drying at 40° C. for 5 h to obtain pre-modified nano zinc oxide; mixing pre-modified nano zinc oxide, diacid monomer, p-toluenesulfonic acid and tetrahydrofuran at a mass ratio of 1:1.5:0.15:15, Stir at 25°C and 250rpm for 25min, add an anti-aging monomer with a molar amount of 1 times that of the diacid monomer, heat to 140°C and continue stirring for 5h, cool naturally to room temperature and filter, wash with anhydrous ethanol and deionized water for 4 times respectively, and dry at 70°C for 7h to obtain modified nano zinc oxide; mix the modified nano zinc oxide, trifluoroacetic acid and methanol in a mass ratio of 1:3.5:20, stir at 25°C and 150rpm in a nitrogen atmosphere for 12h, filter, and heat and filter with an oil pump for 6h to obtain functionalized nano zinc oxide;
[0098] (4) 3,5-diformylphenylboric acid, glacial acetic acid and anhydrous ethanol were mixed in a mass ratio of 1:0.015:9, stirred at 50°C and 150 rpm for 25 min in a nitrogen atmosphere, and 4-amino-2-hydroxy-1,1,1-trifluorobutane (2 times the molar amount of 3,5-diformylphenylboric acid) was added at a uniform rate within 60 min, the temperature was raised to 60°C and refluxed for 2 h, ice deionized water was added and cooled until the precipitate mass remained unchanged, then filtered, washed with anhydrous ethanol 4 times, and dried at 50°C for 12 h to obtain a diol monomer;
[0099] (5) polytetrahydrofuran ether diol, diol monomer and dibutyltin dilaurate were mixed in a molar ratio of 1:0.5:0.015, stirred at 55°C and 250 rpm for 15 min in a nitrogen atmosphere, heated to 80°C, and added with isophorone diisocyanate in an amount twice the molar amount of polytetrahydrofuran diol, and stirred for 2.5 h, and cooled to 35°C to obtain a modified polyurethane;
[0100] (6) The modified polyurethane, functionalized nano zinc oxide and deionized water were mixed in a mass ratio of 1:0.04:0.15, and stirred at 25°C and 600 rpm for 25 min to obtain a plastic track glue solution.
[0101] Test Case
[0102] 1. Anti-aging, self-repairing and water resistance
[0103] Test method: The plastic track glue obtained in each embodiment and the comparative example are coated on a glass plate respectively, and peeled off after curing at 60°C for 12 hours. According to GB / T1040, the dumbbell-shaped specimens of 2mm×35mm are cut and measured with an electronic universal testing machine at 200mm / min. The tensile strength σ0 of the specimen is measured; the tensile strength σ1 of the specimen is measured at 50°C for 360 hours under ultraviolet irradiation in an ultraviolet aging box, and the tensile strength decrease rate is calculated as σ0-σ1 / σ0*100%; the specimen is cut in the middle, and the cross section is pressed by hand to make it close, and it is placed at 60°C for 10 hours to measure the tensile strength σ2 of the specimen, and the tensile strength repair rate is calculated as σ2 / σ0*100%; the specimen is soaked in deionized water for 3 hours, the tensile strength σ3 of the specimen is measured, and the water resistance is calculated as σ3 / σ0*100%;
[0104] 2. Wear resistance
[0105] Test method: The plastic track glue obtained in each embodiment and the comparative example are coated on the glass plate respectively, and then peeled off after curing at 60°C for 12 hours. According to GB / T3960, the samples are cut into 30mm×7mm size and weighed m0. After the friction performance test is carried out with M-200 friction and wear testing machine, m1 is weighed again, and the wear rate is calculated as m0-m1 / m0*100%.
[0106] Table 1 below shows the analysis results of the anti-aging, wear resistance, water resistance and self-repairing properties of the plastic track adhesives of Examples 1 to 3 of the present invention and Comparative Examples 1 to 5.
[0107] Table 1
[0108] Tensile strength decrease rate % Tensile strength repair rate % Water resistance % Wear rate % Example 1 10.6 83 91.9 12.8 Example 2 10.2 86 92.2 12.3 Example 3 10.9 85 91.4 12.6 Comparative Example 1 69.4 82 90.4 12.9 Comparative Example 2 68.7 83 90.2 31.4 Comparative Example 3 11.3 49 90.6 13.1 Comparative Example 4 10.9 12 79.1 12.9 Comparative Example 5 11.1 47 90.7 27.8
[0109] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 5 in Table 1, it can be found that the plastic track glue prepared by the present invention has good anti-aging, wear resistance, water resistance and self-repairing properties.
[0110] By comparison, the tensile strength decrease rate of Examples 1, 2, and 3 is lower than that of Comparative Example 1, which indicates that the diacid monomer and the anti-aging monomer are polymerized on the surface of the pre-modified nano-zinc oxide, and a hindered phenol structure capable of capturing free radicals is introduced on the nano-zinc oxide, which cooperates with the effect of nano-zinc oxide in shielding and scattering ultraviolet light, thereby improving the anti-aging property.
[0111] By comparison, the tensile strength decrease rate and wear rate of Examples 1, 2 and 3 are lower than those of Comparative Example 2, which indicates that the diacid monomer and the anti-aging monomer are polymerized on the surface of the pre-modified nano zinc oxide, and the pyridine in the anti-aging monomer can complex metal ions, enhance the bonding ability between the runway rubber and the substrate, and improve the wear resistance.
[0112] By comparison, the tensile strength repair rates of Examples 1, 2, and 3 are higher than those of Comparative Example 3, indicating that 2,2-dimethoxypropane is used to protect the catechol structure on 2,3-dihydroxyterephthalic acid to avoid the influence of subsequent esterification reactions. After the reaction is completed, the protection is removed to form a reversible borate ester bond with the boric acid group on the modified polyurethane, thereby constructing a covalent cross-linked network of borate ester bonds and improving self-healing properties.
[0113] By comparison, the tensile strength repair rate and water resistance of Examples 1, 2, and 3 are higher than those of Comparative Example 4, which shows that the diol monomer obtained by the Schiff base reaction participates in the polymerization of the polyurethane main chain, and the boric acid group and trifluoromethyl group are introduced to react with catechol and 1,3-diol to form a covalent cross-linked network of borate ester bonds, thereby improving the self-healing performance; at the same time, the highly electronegative and highly stable carbon-fluorine bonds can improve the water resistance.
[0114] By comparison, the tensile strength repair rate of Examples 1, 2, and 3 is higher than that of Comparative Example 5, and the wear rate is lower, which indicates that the 1,3-diol structure on the microcrystalline cellulose forms a reversible borate ester bond with the boric acid group, thereby increasing the covalent cross-linked network of the borate ester bond. At the same time, the microcrystalline cellulose network itself can improve the structural stability, reduce the damage caused by external pressure or friction, and improve the self-healing property and wear resistance.
[0115] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A plastic track glue, characterized in that: The plastic track glue is obtained by mixing modified polyurethane, functionalized nano zinc oxide, microcrystalline cellulose and deionized water; The modified polyurethane is obtained by reacting isophorone diisocyanate, polytetramethylene ether diol and diol monomer; The diol monomer is obtained by reacting 3,5-diformylphenylboronic acid and 4-amino-2-hydroxy-1,1,1-trifluorobutane; The functionalized nano zinc oxide is obtained by reacting nano zinc oxide with hydroxymethyltriethoxysilane, polymerizing a diacid monomer and an anti-aging monomer, and then deprotecting the monomer. The diacid monomer is obtained by reacting 2,3-dihydroxyterephthalic acid and 2,2-dimethoxypropane; The anti-aging monomer is obtained by reacting (4-aminopyridine-2,6-diyl) dimethanol and 3,5-di-tert-butyl-4-hydroxybenzaldehyde.
2. A method for preparing a plastic track glue, characterized in that: The method comprises the following preparation steps: (1) 2,3-dihydroxyterephthalic acid, 2,2-dimethoxypropane, p-toluenesulfonic acid and ethylenediamine are mixed in a mass ratio of 1: (0.6-0.8): (0.004-0.006): (4-6), stirred at 20-30° C. and 200-300 rpm for 4-6 hours, sodium bicarbonate in an amount of 0.2-0.3 times the mass of 2,3-dihydroxyterephthalic acid is added, stirring is continued for 15-25 minutes, then filtered, concentrated under reduced pressure, dichloromethane in an amount of 3-5 times the mass of 2,3-dihydroxyterephthalic acid is added, the mixture is allowed to stand for 1-2 hours, filtered, washed with deionized water for 3-5 times, dried with anhydrous magnesium sulfate for 15-25 minutes, concentrated under reduced pressure, and dried at 55-65° C. for 6-8 hours to obtain a diacid monomer; (2) mixing (4-aminopyridine-2,6-diyl) dimethanol, 3,5-di-tert-butyl-4-hydroxybenzaldehyde, acetic acid and methanol in a mass ratio of 1:(1-2):(0.3-0.5):(10-20), stirring at 70-80° C. and 100-200 rpm for 23-25 h, naturally cooling to room temperature and filtering, washing with methanol and deionized water for 3-5 times respectively, and drying at 55-65° C. for 11-13 h to obtain an anti-aging monomer; (3) mixing nano zinc oxide and 60-70% ethanol solution by volume in a mass ratio of 1:(15-25), ultrasonically dispersing at 20-30° C. for 25-35 min, adding 2-3 times the mass of nano zinc oxide hydroxymethyl triethoxysilane hydrolyzate at a uniform rate within 1-2 h, stirring at 150-250 r / min for 3-5 h, filtering, washing with anhydrous ethanol for 3-5 times, and drying at 35-45° C. for 4-6 h to obtain pre-modified nano zinc oxide; Pre-modified nano zinc oxide, diacid monomer, p-toluenesulfonic acid and tetrahydrofuran are mixed in a mass ratio of 1: (1-2): (0.1-0.2): (10-20), stirred at 20-30° C. and 200-300 rpm for 20-30 min, an anti-aging monomer with a molar amount of 1 times that of the diacid monomer is added, the temperature is raised to 135-145° C. and stirring is continued for 4-6 h, naturally cooled to room temperature and filtered, washed with anhydrous ethanol and deionized water for 3-5 times respectively, and dried at 65-75° C. for 6-8 h to obtain modified nano zinc oxide; modified nano zinc oxide, trifluoroacetic acid and methanol are mixed in a mass ratio of 1: (3-4): (15-25), stirred at 20-30° C. and 100-200 rpm in a nitrogen atmosphere for 11-13 h, filtered, and heated and filtered with an oil pump for 5-7 h to obtain functionalized nano zinc oxide; (4) 3,5-diformylphenylboric acid, glacial acetic acid and anhydrous ethanol are mixed in a mass ratio of 1:(0.01-0.02):(8-10), stirred at 100-200 rpm for 20-30 min in a nitrogen atmosphere at 45-55° C., and 4-amino-2-hydroxy-1,1,1-trifluorobutane (2 times the molar amount of 3,5-diformylphenylboric acid) is added at a uniform rate within 55-65 min, the temperature is raised to 55-65° C., and refluxed for 1-3 h, ice deionized water is added to cool until the precipitate mass remains unchanged, and then filtered, washed with anhydrous ethanol for 3-5 times, and dried at 45-55° C. for 11-13 h to obtain a diol monomer; (5) Mix polytetrahydrofuran ether diol, diol monomer and dibutyltin dilaurate in a molar ratio of 1:(0.4-0.6):(0.01-0.02), stir for 10-20 min at 50-60° C. and 200-300 rpm in a nitrogen atmosphere, raise the temperature to 75-85° C., add isophorone diisocyanate in an amount of 1.5-2.5 times the molar amount of polytetrahydrofuran diol, continue stirring for 2-3 h, and cool to 30-40° C. to obtain a modified polyurethane; (6) The modified polyurethane, functionalized nano zinc oxide, microcrystalline cellulose and deionized water are mixed in a mass ratio of 1:(0.03-0.05):(0.02-0.04):(0.1-0.2), and stirred at 20-30° C. and 550-650 rpm for 20-30 min to obtain a plastic track glue solution.
3. The method for preparing a plastic track glue according to claim 2, characterized in that: The reaction equation of the diacid monomer in step (1) is:
4. The method for preparing a plastic track glue according to claim 2, characterized in that: The reaction equation of the anti-aging monomer in step (2) is:
5. The method for preparing a plastic track glue according to claim 2, characterized in that: The hydroxymethyltriethoxysilane hydrolyzate in step (3) is obtained by mixing hydroxymethyltriethoxysilane and deionized water in a mass ratio of 1:124 and hydrolyzing at 25° C. for 30 minutes.
6. The method for preparing a plastic track glue according to claim 2, characterized in that: The reaction equation of the pre-modified nano zinc oxide in step (3) is:
7. The method for preparing a plastic track glue according to claim 2, characterized in that: The reaction equation of the functionalized nano zinc oxide in step (3) is:
8. The method for preparing a plastic track glue according to claim 2, characterized in that: The reaction equation of the diol monomer in step (4) is:
9. The method for preparing a plastic track glue according to claim 2, characterized in that: The reaction equation of the modified polyurethane in step (5) is: Where R1 is 10. A plastic track, characterized in that: The plastic track glue of the plastic track is the plastic track glue described in any one of claims 1 to 9.
Citation Information
Cited By
Preparation method of low-VOC (volatile organic compound) polyurethane structural adhesive
CN121427488A
